Level of knowledge and attitude toward sexuality in pregnant adolescent Hospital Central Universitario Dr. Antonio María Pineda (Boletin Médico de Postgrado, 2022)
Early sexual activity in adolescence represents a public health problem due to the consequences it entails, such as teenage pregnancy, an increase in sexually transmitted diseases and the family, economic and social problems it entails. The present study was conducted with the aim of determining the level of knowledge and attitudes about sexuality in a group of pregnant adolescents who were admitted to the Department of Obstetrics and Gynecology of the Dr. Antonio María Pineda Central University Hospital during the period January-December 2019. The average age of the patients was 15.6 years old. 62% of patients surveyed showed a low level of knowledge about sexuality. In relation to the level of knowledge about sexuality by dimensions, the patients showed a high level of knowledge about anatomy and physiology, sexual and reproductive of the adolescent but a low level of knowledge about sexual response cycle, prevention of sexually transmitted infections and contraceptive methods as an alternative to prevent pregnancy. Regarding the identification of attitudes about sexuality, most of the adolescents showed favorable sexual attitudes in all the dimensions studied.